Rock-a-bye farm - Hamm, Diane Johnston; Brown, Rick, 1946- (New York : Simon & Schuster Books for Young Readers, 1992)
The farmer helps his family and barnyard animals fall asleep before drifting off himself.
Keywords: Sleep -- Juvenile fiction; Sleep -- Fiction